Strong anisotropy effect in an iron-based superconductor CaFe0.882Co0.118AsF. (8th June 2017) - Ma, Yonghui; Ji, Qiucheng; Hu, Kangkang; Gao, Bo; Li, Wei; Mu, Gang; Xie, Xiaoming
Abstract: The anisotropy of iron-based superconductors is much smaller than that of the cuprates and that predicted by theoretical calculations. A credible understanding for this experimental fact is still lacking up to now. Here we experimentally study the magnetic-field-angle dependence of electronic resistivity in the superconducting phase of an iron-based superconductor CaFe 0.882 Co 0.118 AsF, and find the strongest anisotropy effect of the upper critical field among the iron-based superconductors based on the framework of Ginzburg–Landau theory. The evidence of the energy band structure and charge density distribution from electronic structure calculations demonstrates that the observed strong anisotropic effect mainly comes from the strong ionic bonding in between the ions of Ca 2+ and F −, which weakens the interlayer coupling between the layers of FeAs and CaF. This finding provides a significant insight into the nature of the experimentally-observed strong anisotropic effect of electronic resistivity, and also paves the way for designing exotic two-dimensional artificial unconventional superconductors in the future.